(untitled) - Knisely, Karin (Sunderland, Mass., 2009)
This book provides practical advice to students who are learning to write according to the conventions in biology. Using the standards of journal publication as a model, the author provides, in a user-friendly format, specific instructions on: using biology databases to locate references; developing sound reading strategies; paraphrasing for improved comprehension; writing for a particular audience with the appropriate tone; preparing lab reports or scientific papers, posters, and oral presentations with accepted format and content; self-evaluating drafts; using peer and instructor feedback for professional development; and preparing oral presentations in PowerPoint.
Keywords: Report writing,Viết báo cáo